2011
DOI: 10.1186/1471-2458-11-140
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for tuberculosis treatment failure, default, or relapse and outcomes of retreatment in Morocco

Abstract: BackgroundPatients with tuberculosis require retreatment if they fail or default from initial treatment or if they relapse following initial treatment success. Outcomes among patients receiving a standard World Health Organization Category II retreatment regimen are suboptimal, resulting in increased risk of morbidity, drug resistance, and transmission.. In this study, we evaluated the risk factors for initial treatment failure, default, or early relapse leading to the need for tuberculosis retreatment in Moro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
106
3
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(138 citation statements)
references
References 10 publications
19
106
3
4
Order By: Relevance
“…The relationship between sex and default, shown previously for drug-susceptible TB, 15,[25][26][27][28] was close to signifi cance. This association may be explained by the fact that in Armenia males are more likely to work outside the home; presumably, once their health improves they seek employment, sometimes outside the country.…”
Section: Discussionmentioning
confidence: 96%
“…The relationship between sex and default, shown previously for drug-susceptible TB, 15,[25][26][27][28] was close to signifi cance. This association may be explained by the fact that in Armenia males are more likely to work outside the home; presumably, once their health improves they seek employment, sometimes outside the country.…”
Section: Discussionmentioning
confidence: 96%
“…[6][7][8][9] Patient characteristics such as male sex, alcoholism and illiteracy, and health system factors such as long distances to TB clinics, lack of anti-tuberculosis drugs, inadequate health education and poor management of drug side effects are risk factors for return after LTFU or retreatment default. [10][11][12][13][14][15] Some studies have identifi ed characteristics of retreatment cases that infl uence…”
Section: Resultsmentioning
confidence: 99%
“…The middle line of the figure shows the results of the current system and indicates a completely downward trend in TB recurrence during 2006 -2016. Compared to the present study, Dooley et al (2011) in Morocco evaluated patients who had a positive smear or culture of pulmonary TB and were retreated. They showed that the success rate of TB treatment increases by implementing DOTS strategy and identifying the risk factors (10).…”
Section: Discussionmentioning
confidence: 99%
“…Each year, relevant indicators are measured to determine the success or failure of programs, and management solutions are presented in the province to address the shortcomings (9,10). …”
Section: Introductionmentioning
confidence: 99%